2021
DOI: 10.3390/molecules26195926
|View full text |Cite
|
Sign up to set email alerts
|

Insights on the Electrocatalytic Seawater Splitting at Heterogeneous Nickel-Cobalt Based Electrocatalysts Engineered from Oxidative Aniline Polymerization and Calcination

Abstract: Given the limited access to freshwater compared to seawater, a growing interest surrounds the direct seawater electrolysis to produce hydrogen. However, we currently lack efficient electrocatalysts to selectively perform the oxygen evolution reaction (OER) over the oxidation of the chloride ions that are the main components of seawater. In this contribution, we report an engineering strategy to synthesize heterogeneous electrocatalysts by the simultaneous formation of separate chalcogenides of nickel (NiSx, x … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Hence, it is interesting the examine whether the formation of real metallic species could change the trends in selectivity during ORR. Indeed, we recently showed that using thermal treatment under an inert atmosphere to generate a reductive environment will lead to the formation of mixture of metals and chalcogenides of NiS x (x = 0, 2/3, 8/9 and 4/3) or CoS x (x = 0 and 8/9) onto a carbon-nitrogen-sulfur nanostructured network [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it is interesting the examine whether the formation of real metallic species could change the trends in selectivity during ORR. Indeed, we recently showed that using thermal treatment under an inert atmosphere to generate a reductive environment will lead to the formation of mixture of metals and chalcogenides of NiS x (x = 0, 2/3, 8/9 and 4/3) or CoS x (x = 0 and 8/9) onto a carbon-nitrogen-sulfur nanostructured network [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…A closer observation conforms the formation of nickel-sulphur or cobalt-sulphur species and that there is no other overlapping between the signals of the metals and oxygen, carbon or nitrogen. For PANI-Ni-TS-TC, the atomic ratio of Ni/S is 1.6 ± 0.1, which suggests the formation of a Ni 3 S 2 phase, while for PANI-Co-TS-TC, the atomic ratio of 1.2 ± 0.1 is in line with the formation of Co 9 S 8 species [ 41 ]. It was previously observed that the length of the tip of the Ni 3 S 2 particles increases with the duration of the calcination step [ 20 ], explained by the so-called vapor-liquid-solid (VLS) mechanism of growth, which involves a vapor of nickel-sulfur, meaning that the super-saturation and nucleation at the liquid/solid interface leads to axial crystal growth [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Transition metal dichalcogenides have been widely developed because of their unique structure and electronic characteristics. [83][84][85] For example, Hajjar et al [86] reported a synthetic method for the synthesis of multiphase OER electrocatalysts by generating independent nickel and cobalt chalcogenides on carbon-nitrogen-sulfur nanocomposites. The synthesized materials were PANI-Ni and PANI-Co (Figure 4a), the target material obtained had excellent OER catalytic activity and relatively lasting stability.…”
Section: Transition Metal Dichalcogenidesmentioning
confidence: 99%
“…a) Sketch of the engineered approach to produce electrocatalysts (Reproduced with permission. [ 86 ] Copyright 2021, American Chemical Society). b) Schematic diagram of the fabrication of NMN‐NF (Reproduced with permission.…”
Section: Non‐noble‐metal‐compound‐based Electrocatalysts For Oxygen E...mentioning
confidence: 99%
“…Therefore, it is imperative to develop and utilize sustainable energy to minimize carbon emissions [ 4 , 5 ]. Hydrogen has a high energy density and generates zero carbon emissions, making it perfect for renewable energy production [ 6 , 7 ]. Among various approaches, hydrogen generation using water electrolysis is an efficient way to obtain pure hydrogen energy [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%